Inhibitory Effect of Moringa oleifera Seed Extract and Its Behenic Acid Component on Staphylococcus aureus Biofilm Formation - Seoyoung Kim; Tae-Jong Kim (Antibiotics)
Background/Objectives: Inhibiting biofilm formation without killing cells facilitates the physical removal of contaminating bacteria while minimizing the opportunity for resistant bacteria to emerge. Results: The M. oleifera methanolic seed extract contained 1.48% behenic acid, significantly inhibiting S. aureus biofilm formation. Although behenic acid did not affect cell growth, it inhibited biofilm formation in a concentration-dependent manner, up to 20 mg/L. The cell physiology changes caused by behenic acid are potentially unrelated to biofilm formation inhibition, as no correlation was noted between cell hydrophobicity, polysaccharide production, extracellular DNA production, or protein production and behenic acid concentration. Thus, it was hypothesized that the surfactant properties of behenic acid contribute to its ability to inhibit biofilm formation, as a similar biofilm-inhibitory effect was observed when S. aureus was administered 1% Tween 80, a surfactant. Methods: A methanolic extract of Moringa oleifera seeds was selected from a library of edible plant extracts to inhibit Staphylococcus aureus biofilm formation without cell killing. Conclusions: Behenic acid is a saturated fatty acid that is used as an ingredient in cosmetics and ointments; thus, behenic acid may benefit the skin by inhibiting the biofilm formation of S. aureus, a commensal skin pathogen.